An investigation of the efficiency of using O2 and H2 (hydrooxile gas -HHO) gas additives in a ci engine operating on diesel fuel and biodiesel. (1st June 2018) - Rimkus, Alfredas; Matijošius, Jonas; Bogdevičius, Marijonas; Bereczky, Ákos; Török, Ádám
Abstract: In a vehicle with a CI (compression ignition) engine, the power of the latter rotates an electric generator to produce a mixture of hydrogen (H2 ) and oxygen (O2 ) gas (hydrooxile – HHO, later just HHO) by water electrolysis. Low HHO content levels in air (0.14–0.18% of the volume) combined with air in cylinders of the CI engine affect the energy and environmental performance of the engine. It was found through stand tests and numerical modeling that chemically active hydrogen starts to ignite at the end of the compression stroke when the pressure and temperature rise prior to fuel injection into the cylinder. Early hydrogen ignition and supplemental energy consumption for HHO gas production worsen the energy performance of the engine and increase concentrations of carbon dioxide (CO2 ) and nitrogen oxide (NOx ) in the exhaust gas. However, H2 and O2 additives reduce concentrations of incomplete combustion products (carbon monoxide (CO) and hydrocarbons (HC)) as well as the smokiness of the exhaust. When diesel fuel is replaced with biodiesel and when HHO gas is added, the indicated efficiency of the engine changes insignificantly; however, concentrations of CO and HC in the exhaust gas and smoke levels are reduced markedly. Highlights: The fuel consumption increases than the energy of producing HHO is supplying from engine electrical generators. H2 gas from O2 and H2 (HHO) gas mixture ignites spontaneously at the end of compression in the CI engine. The using of HHO in CI engine increases the CO2 and NOx pollution in the exhaust.